Fusobacterium nucleatum upregulates the immune inhibitory receptor PD-L1 in colorectal cancer cells via the activation of ALPK1 - Coco Duizer; Moniek Salomons; Merel van Gogh; Sanne Gräve; Freke A. Schaafsma; Maaike J. Stok; Merel Sijbranda; Raghuvandhanan Kumarasamy Sivasamy; Rob J. L. Willems; Marcel R. de Zoete (Gut Microbes)
Fusobacterium nucleatum is a Gram-negative oncobacterium that is associated with colorectal cancer. The molecular mechanisms utilized by F. nucleatum to promote colorectal tumor development have largely focused on adhesin-mediated binding to the tumor tissue and on the pro-inflammatory capacity of F. nucleatum. However, the exact manner in which F. nucleatum promotes inflammation in the tumor microenvironment and subsequent tumor promotion remains underexplored. Here, we show that both living F. nucleatum and sterile F. nucleatum-conditioned medium promote CXCL8 release from the intestinal adenocarcinoma HT-29 cell line. We determined that the observed pro-inflammatory effect was ALPK1-dependent in both HEK293 and HT-29 cells and that the released F. nucleatum molecule had characteristics that match those of the pro-inflammatory ALPK1 ligand ADP-heptose or related heptose phosphates. In addition, we determined that not only F. nucleatum promoted an ALPK1-dependent pro-inflammatory environment but also other Fusobacterium species such as F. varium, F. necrophorum and F. gonidiaformans generated similar effects, indicating that ADP-heptose or related heptose phosphate secretion is a conserved feature of the Fusobacterium genus. By performing transcriptional analysis of ADP-heptose stimulated HT-29 cells, we found several inflammatory and cancer-related pathways to be differentially regulated, including DNA mismatch repair genes and the immune inhibitory receptor PD-L1. Finally, we show that stimulation of HT-29 cells with F. nucleatum resulted in an ALPK1-dependent upregulation of PD-L1. These results aid in our understanding of the mechanisms by which F. nucleatum can affect tumor development and therapy and pave the way for future therapeutic approaches.